2000
DOI: 10.1161/01.res.86.11.1129
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Reverts Dysfunction of Endothelial Nitric Oxide Synthase

Abstract: 5-methyltetrahydrofolate (MTHF), the active form of folic acid, has been reported to restore NO status in hypercholesterolemic patients. The mechanism of this effect remains to be established. We assessed the effects of L- and D-MTHF on tetrahydrobiopterin (BH(4))-free and partially BH(4)-repleted endothelial NO synthase (eNOS). Superoxide production of eNOS and the rate constants for trapping of superoxide by MTHF were determined with electron paramagnetic resonance using 5-diethoxyphosphoryl-5-methyl-1-pyrro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
177
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(192 citation statements)
references
References 58 publications
11
177
2
2
Order By: Relevance
“…21 Folate can increase the levels of the proangiogenic molecule nitric oxide (NO) by regenerating the endothelial NO synthase cofactor, tetrahydrobiopterin (BH 4 ). 22 Studies in knockout mice in which the mouse ortholog of FH(PSA)1 was eliminated, the mice had a dramatically reduced ability to undergo angiogenesis of a subcutaneously introduced Matrigel plug. Endothelial cells derived from the knockout mice had less ability for b 1 integrin activation.…”
Section: Discussionmentioning
confidence: 99%
“…21 Folate can increase the levels of the proangiogenic molecule nitric oxide (NO) by regenerating the endothelial NO synthase cofactor, tetrahydrobiopterin (BH 4 ). 22 Studies in knockout mice in which the mouse ortholog of FH(PSA)1 was eliminated, the mice had a dramatically reduced ability to undergo angiogenesis of a subcutaneously introduced Matrigel plug. Endothelial cells derived from the knockout mice had less ability for b 1 integrin activation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, methylfolate itself may have a direct effect on blood pressure via a mechanism independent of transsulphuration metabolites such as Hcy. It has been suggested that reduced folates may interact synergistically with tetrahydrobiopterin metabolism in the synthesis of NO by endothelial nitric oxide synthase (Hayden and Tyagi 2004;Moat et al 2004;Stroes et al 2000;Hyndman et al 2002;Doshi et al 2003) and as such help to maintain vascular wall elasticity. Taken collectively, the dietary, metabolite and genetic findings suggest a clear influence of H 2 S-related transsulphuration parameters on blood pressure and warrant further studies to better characterise this important new area of clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…31 The active form of folic acid, 5-methyltetrahydrofolate, restores BH 4 to allow participation in eNOS reactions. 12 When BH 4 is not available, eNOS generates superoxide radicals, 31 which impair endothelial proliferation. 32,33 Folic acid and its metabolites are also superoxide radical scavengers.…”
Section: Psma Expression In Tumor Neovasculaturementioning
confidence: 99%
“…It is possible that the folate hydrolase activity of PSMA is important in facilitating vasculogenesis in these tissues, as well as in neoplastic neovasculature, by increasing the availability of folate, which can increase the levels of the proangiogenic molecule nitric oxide (NO) by regenerating the endothelial nitric oxide synthase (eNOS) cofactor, tetrahydrobiopterin (BH 4 ). 12 In this study, we investigate the expression of PSMA in neovasculature associated with nonneoplastic reparative and regenerative human tissues.…”
mentioning
confidence: 99%